Pengaruh Stres Kerja Dan Komunikasi Terhadap Kinerja Karyawan PT. POS Indonesia Cabang Malang - Sonia Nengsih; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT This study aims at the description of Job Stress, Communication and Performance, Effects of Job Stress and Communication, Effects of Job Stress, and the Effect of Communication on Employee Performance at PT. Pos Indonesia Malang Branch. Population and sample are all members of the population of 68 people. Data collection techniques using questionnaires using the Likert scale assessment. Data analysis used multiple linear regression using SPSS.The results of the analysis show that work and communication stress affects employee performance, partially job stress has a negative effect on employee performance and Communication has an effect on the performance of employees of PT. Pos Indonesia Malang Branch. Communication becomes a medium for delivering information in order to create a good climate of performance among employees with superiors or employees with employees. Keywords: Job stress, Communication, and employee perform